Financial education versus costly counseling: how to dissuade borrowers from choosing risky mortgages? - Agarwal, Sumit, Gene Amromin, Itzhak Ben-David and Douglas D. Evanoff (American Economic Journal: Economic Policy)
This paper explores the effects of mandatory third-party review of mortgage contracts on consumer choice. The study is based on a legislative pilot carried out in Illinois in 2006, under which mortgage counseling was triggered by applicant credit scores or by their choice of "risky mortgages." Low-credit score applicants for whom counselor review was mandatory did not materially alter their contract choice. Conversely, higher credit score applicants who could avoid counseling by choosing nonrisky mortgages did so, decreasing their propensity for high-risk contracts between 10 and 40 percent. In the event, one of the key goals of the legislation$1 (Bcurtailment of high-risk mortgage products$1 (Bwas only achieved among the population that was not counseled. - Reproduceds
Keywords: Household Saving, Banks, Depository Institutions, Micro Finance Institutions, Mortgages